EFFECTIVENESS OF EPRIN FOR STRONGILATE INVASION OF GOATS - Антіпов, Анатолій; Селих, Інна; Човгун, Аліна; Пересунько, Олена; Єрохіна, Олена (Modern engineering and innovative technologies, 2023)
Our research established that out of 40 examined goats belonging to a private farm in the Taraschan district, 30 heads were affected by strongylids. The extent of infestation was 75.0%, and the intensity of infestation, which was determined by counting th